2009
DOI: 10.1681/asn.2008111199
|View full text |Cite
|
Sign up to set email alerts
|

A Recessive Gene for Primary Vesicoureteral Reflux Maps to Chromosome 12p11-q13

Abstract: Primary vesicoureteral reflux (pVUR) is one of the most common causes of pediatric kidney failure. Linkage scans suggest that pVUR is genetically heterogeneous with two loci on chromosomes 1p13 and 2q37 under autosomal dominant inheritance. Absence of pVUR in parents of affected individuals raises the possibility of a recessive contribution to pVUR. We performed a genome-wide linkage scan in 12 large families segregating pVUR, comprising 72 affected individuals. To avoid potential misspecification of the trait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 46 publications
0
36
1
Order By: Relevance
“…We did not find linkage in the region on chromosome 12 reported by Weng et al 15 Seven families contributed to the locus reported by Weng et al: Four Hasidic Jewish, two Italian, and an Irish American but with the major contribution coming from two of the Hasidic Jewish families. The authors postulated that this locus could be important in families of various ethnic origins, but it does not seem to account for a significant proportion of families in either of the populations we have studied.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…We did not find linkage in the region on chromosome 12 reported by Weng et al 15 Seven families contributed to the locus reported by Weng et al: Four Hasidic Jewish, two Italian, and an Irish American but with the major contribution coming from two of the Hasidic Jewish families. The authors postulated that this locus could be important in families of various ethnic origins, but it does not seem to account for a significant proportion of families in either of the populations we have studied.…”
Section: Discussioncontrasting
confidence: 72%
“…The high incidence in offspring of affected individuals and the large number of pedigrees consistent with autosomal dominant inheritance, albeit with reduced penetrance, is in keeping with a dominant model; however, recently, a locus was identified on 12p11-q13 using a recessive model. 15 Here we report on linkage and association analysis in affected sibling pairs from two populations. We used the Affymetrix NspI array to generate genome-wide data, adding in haplotype-tagging single-nucleotide polymorphisms (SNPs) to obtain full coverage for six candidate genes: AGTR2, HNF1B, PAX2, RET, ROBO2, and UPK3A.…”
mentioning
confidence: 99%
“…[75][76][77] Fortunately for human geneticists, and also those studying the basic mechanisms of renal tract development, there is open access to a resource that makes high-throughput analyses of gene expression freely available to all. The GenitoUrinary Development Molecular Anatomy Project 78 database holds information on RNA array analyses from microdissected tissues in the developing murine urogenital system.…”
Section: Ongoing Discovery Of Novel or Unsuspected Ureter Developmentmentioning
confidence: 99%
“…22,47,129 However, dominant as well as recessive models were used to analyze 72 vur-affected individuals from 12 large families in a study by weng et al 26 whereas the dominant model yielded no signals across the entire genome, a unique linkage peak on chromosome 12p11-q13 was found in the recessive model and was confirmed by fine mapping. 26 although the clinically observed increased risk of vur in siblings of index cases and the high transmission from parents to children suggest that vur is not generally inherited in a recessive fashion, the data suggest that there may be a recessive form of the disorder. interestingly, two large families in this study failed to yield a significant logarithm (base 10) of odds (LOD) score across the entire genome under either a recessive or a dominant model, possibly suggesting that vur in these particular families might be caused by multiple risk alleles segregating along different lines of descent.…”
Section: N a T U R E R E V I E W S U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…it has become increasingly evident that the familial clustering of vur must have a genetic basis; however, to date there has been no agreement on the mode of inheritance. a range of inheritance patterns have been suggested, including autosomal dominant with incomplete penetrance, [20][21][22][23][24] autosomal recessive, 25,26 X-linked 27,28 and polygenic, 29 and a substantial amount of work has evaluated candidate genes and conducted genome-wide scans. However, an understanding of the genetics of primary vur remains elusive.…”
Section: Introductionmentioning
confidence: 99%